Detection of contamination with parasitic helminthes eggs on vegetables grown on selected pieces of lands in Lattakia governorate - الأبكع, ريف; أمل إبراهيم ديوب, (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted on vegetables produced on agricultural lands in Lattakia governorate, which were irrigated from two water sources; Lands in Al-Amruniyah village/Al-Bahlauliyah area/, irrigated from waters of AL- Kabeer AL-Shamali River. The second lands were located in north of Lattakia, at Al-Qanjarah village, irrigated from Al-Qanjarah dam. This study aimed to confirm whether a contamination on vegetables by parasitic helminthes eggs was existed or not. This is considered as an important bio-indicator for the quality of water used for irrigation. Eight different species of vegetables (Cucumic Sativus, Beta Vulgaris, Petroselinum crispum, Capsicum, Raphanus sativus, Vicia faba, Mentha piperita, Vitis vinifera) were collected during winter and spring seasons 2023-2024 via two visits. Some of which are eaten fresh, while others are cooked. Vegetables were examined in vitro using globally approved laboratory methods to investigate parasitic eggs on vegetables. The results of the microscopic examination showed the presence of parasitic helminthes eggs on the collected samples. These were Ascaris lumbricoides, Hymenolepis diminuta, Enterobius vermicuaris, Fasciola hepatica, Diphyllobothrium latum, and Ancylostoma duodenale. The total count of eggs isolated from the collected samples during the spring and winter seasons reached 40 eggs. The largest contamination of eggs was 25/40 eggs on vegetables collected from agricultural land in AL- Amruniya village, which was irrigated from the waters of the AL- kabeer AL-shamali River, compared to 15/40 eggs isolated from vegetables collected from Al-Qanjarah village , which was irrigated from the waters of Al-Qanjarah dam. The results also showed that Fasciola hepatica eggs were more predominant on studied vegetables collected from two areas, with general total count of 16 eggs (40%), followed by Ascaris lumbricoides 8 eggs (20%), and Hymenolepis diminuta 6 eggs (15%). It was also found that eggs were more prevalent on vegetables collected in spring compared to winter. It was also found that pepper and grape leaves were mainly contaminated with eggs, followed by beans and radishes, then chard, mint and cucumber, respectively, whilst no eggs were recorded on parsley during the same study period.